Positive effect of specific low-frequency electrical stimulation during short-term recovery on subsequent high-intensity exercise - Bieuzen, F.; Borne, R.; Toussaint, J. -F.; Hausswirth, C. (Applied Physiology, Nutrition, and Metabolism, 2014)
The objective of this study was to test how low-frequency electrical stimulation (LFES; Veinoplus Sport (AdRem Technology, Paris, France)) of the calf muscles affects recovery indices compared with 2 other commonly used recovery methods (active, ACT; passive, PAS). The tests used assessed predominantly anaerobic performance after short-term (15 min) recovery, and the kinetics of blood markers. Fourteen highly trained female handball players completed 2 Yo-Yo Intermittent Recovery tests (level 2; YYIR2) separated by a 15-min recovery period. During recovery, 1 of 3 recovery methods (ACT, LFES or PAS) was randomly selected. Performance (i.e., distance run) was measured at the end of each YYIR2 test. Blood lactate, pH, bicarbonate concentrations, heart rate, respiratory gas exchange and tissue saturation index for the lateral gastrocnemius were recorded. LFES showed a very likely beneficial effect on performance during the second YYIR2 relative to PAS and a possible beneficial effect relative to ACT (distance Pre vs. Post; LFES: -1.8%; ACT: -7.6%; PAS: -15.9%). Compared with PAS recovery, LFES and ACT recovery clearly showed a faster return to baseline for blood lactate, pH and bicarbonate concentrations during the recovery period. LFES of the calf muscles and, to a lesser extent, ACT recovery appear to effectively improve short-term recovery between 2 bouts of exhausting exercises. These methods could be of benefit if applied during half-time, for sports involving successive rounds, or where only a limited recovery period is available.